Perspectives of the methods’ developments for the functional diagnosis of nasal breathing - Носова, Я. В.; Semenets, V. V.; Shushliapina, N. O.; Ibrahim Younouss Abdelhamid; Аврунін, О. Г.; Семенець, В. В. (RS Global Sp. z O.O., 2018)
Perspectives of development of methods for functional diagnostics of nose respiration are described. For the development of modern rhinomanometry, primary tasks are not only metrological provision with means of measuring airflow indicators, but also methodological, minimizing processing errors, errors arising from one-time measurements and incorrect averaging of data. An important role here should be played by information technologies, which reduce uncertainty in measurements, by taking into account the properties of the test object, methods of automated processing, analysis and interpretation of diagnostic data.
Keywords: hinomanometry; nasal breathing; flow rate; differential pressure